Expression of individual mutations and haplotypes in the galactocerebrosidase gene identified by the newborn screening program in New York State and in confirmed cases of Krabbe's disease. Issue 11 (November 2016) - Saavedra‐Matiz, Carlos A.; Luzi, Paola; Nichols, Matthew; Orsini, Joseph J.; Caggana, Michele; Wenger, David A.
Abstract : Newborn screening (NBS) for Krabbe's disease (KD) has been instituted in several states, and New York State has had the longest experience. After an initial screening of dried blood spots, samples from individuals with galactocerebrosidase (GALC) values below a given cutoff level were subjected to additional testing, including sequencing of the GALC gene. This resulted in the identification of mutations that had previously been found in confirmed KD patients and of variants that had never previously been reported. Some individuals had variants considered to be polymorphisms, alone or on the same allele as another mutation. To help with counseling of families on the risk for a newborn to develop KD, expression studies were conducted with these variants identified by NBS. GALC activity was measured in COS1 cells for 140 constructs and compared with mutations that had previously been seen in confirmed cases of KD. When a polymorphism was present on the same allele as the variant, expressed activity was measured with and without the polymorphism. In some cases the presence of the polymorphism greatly lowered the measured GALC activity, possibly making it disease causing. Although it is not possible to predict conclusively whether a variant is severe and will result in infantile KD if two such variants are present or whether a variant is mild and will result in late‐onset disease, some variants clearly are not disease causing. This is the largest expression study of GALC variants/mutations found in NBS and confirmed KD cases. This work will be helpful for counseling families of screen‐positive newborns found to have low GALC activity. © 2016 Wiley Periodicals, Inc. Abstract : Expression studies of mutations and haplotypes found in the GALC gene of known patients with KD show a good correlation between severity of the mutation and residual activity measured. With this method, mutations found in individuals identified in newborn screening can be tested to assess whether the mutation is disease causing. The graph shows expression studies of representative mutations.